Acceptance towards space maintainer in paediatric population with premature primary tooth loss- an institutional study - SUNIL, NURUL SYAMIMI BINTI MOHD AZLAN; JESSY P. M.D.S.; DURAISAMY M.D.S., REVATHI (The journal of contemporary issues in business and government, 2020)
Space maintainers are the most commonly used appliance for interceptive orthodontics. Space maintainer is mainly used when there is premature loss of deciduous molar to eliminate or reduce the severity of developing malocclusion.The aim of this study was to evaluate the acceptance of space maintainer in paediatric patients undergoing extraction of early loss of primary teeth. This study included children below the age of 9 years, both male and female, reported to Saveetha Dental College between June 2019 to March 2020 with the history of primary tooth extraction. Inclusion criteria included paediatric patients below 9 years of age who were indicated for space maintainers. Exclusion criteria included adult patients, medically-compromised patients, patients with special care needs and patients with congenital missing teeth. A total of around 1700 patient records were reviewed and analysed for the inclusion criteria and the following parameters were gathered; patients’ age, gender, patients acceptance towards space maintainer and type of space maintainer given. Data was recorded in Microsoft Office Excel (2013) and analysed using SPSS Software Version 26.0. Chi-square test was done to find out correlation between variables. Significant level test was set at p<0.05. The results proved that a total of 702 children indicated for space maintainers. Acceptance of space maintainer was observed in 10.3% of patients.Statistically significant association was found in acceptance of space maintainer between age groups (p<0.05). Within the limits of this study, it is concluded that 10.3% acceptance of space maintainer was found among patients. Children with 6 years of age had a favourable acceptance towards space maintainers. The deleterious effect in non acceptance space maintainer and awareness about the preventive orthodontics should be instilled among parents and children.